Description of Treatment Outcomes among Pulmonary Tuberculosis Patients in Bandung City in 2014 - Hamdan, Syafinaz; Rohmawaty, Enny; Lestari, Bony Wiem (Althea Medical Journal, 2017)
Background: Pulmonary Tuberculosis (pulmonary TB) is an infectious lung disease which is still a major health problem in the world. In Indonesia, pulmonary TB treatment outcomes are monitored and assessed in Directly Observed Treatment Short Course (DOTS) as an indicator of national TB control program performance. Therefore, the study was conducted to determine the treatment outcomes among pulmonary TB patients in Bandung City.Methods: This cross-sectional study was conducted using secondary data. The sample sizes were 1,598 pulmonary TB patients taken by total sampling with data collected from TB Registration database of Bandung city at Infectious Disease Control Unit, Bandung City Health Office (Unit Kontrol Penyakit Menular, Dinas Kesehatan Kota Bandung) from January to December 2014. The treatment outcomes were classified as successful (cured and treatment completed) and unsuccessful (failed, defaulted, and died).Results: Out of the 1,598 TB patients, most of the respondents were male, aged 15â24 years old and from Public Health Center (Pusat Kesehatan Masyarakat, Puskesmas) and hospital. A total of 1,008 treatments (63.08%) were cured, 292 (18.27%) were completed, 47 (2.94%) were failed, 211 (13.21%) were defaulted, and 40 (2.50%) were died. Total of transferred outpatients were 134 andÂ  not considered as treatment outcome.Conclusions: From the results, it can be concluded that 81.35% and 18.65% were considered as successful and unsuccessful outcome respectively, thus, did not achieve WHO target of 85%. Therefore, DOTS program implemented in Bandung City should be reviewed to improve success rate of the treatment outcome.